Analysis of the Dynamics of Hedonic Shopping Motivation of High School Learners - Nabila; Netda Kostantia Mauwa; Christin Finda Nante; Ji Suk Young; Bambang Ismanto (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2025)
The dynamics of hedonistic behavior of high school students in the era of information technology development greatly influences their lifestyle. The aim of this research is to determine the hedonistic lifestyle of students in terms of spending tendencies and the teacher's perspective in dealing with the dynamics of a hedonistic lifestyle. This research uses a Mixed Methods approach, integrating quantitative and qualitative methods. Data was collected through questionnaires, interviews, observations and document studies of class XI students at SMAS Karya Dharma Veteran Sambi. The results of this research show that students' hedonistic lifestyle is dominated by the value shopping indicator (4.31) in the very high category. Teachers identify the negative impacts of hedonism, such as low self-discipline and increased consumer behavior. To overcome this, teachers suggest moral guidance programs, controlling hedonistic behavior through counseling, and collaborating with parents. These findings provide insight into the importance of collaboration between teachers, schools and families in directing students' lifestyles in a more positive direction. Keywords: Hedonistic lifestyle, Shopping motivation, Student behavior, Character education, Counseling guidance